The effect of COVID-19 infection on nasal mucociliary clearance in health care workers in tertiary care hospital: a cross sectional study - Bhaskaran K., Sajitha; Thomas, Norma; Balakrishnan, Vibha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Mucociliary clearance is the primary innate defence mechanism of the respiratory tract and protects the respiratory tract from foreign bodies such as small particles, dust, and pathogens. The saccharin test is an useful screening technique for measuring nasal mucociliary clearance as it is inexpensive, simple to do, and reproducible. The objective of the study was to determine whether severe acute respiratory syndrome (SARS-CoV-2) (COVID-19) has an effect on nasal mucociliary clearance. Methods: Our study was conducted in 100 health care workers. In these 50 health care workers, with post covid status of 2 weeks, who were tested positive for SARS-CoV-2 by RTPCR, has taken as cases. 50 health care workers without SARS-CoV-2 infection taken as control group. The mucociliary clearance assessed by calculating NMC time using saccharine test. Results: We did not find a statistically significant difference between the groups in terms of NMC duration. Conclusions: Mucociliary clearance is an important airway defence mechanism.though few viral infections prolong the NMC duration, in our study, we did not find a statistically significant difference between the groups in terms of NMC duration. There was no correlation between age, sex, covid symptoms (loss of smell/taste) and NMC.